Development of Pocket Book of Character Education Of Nautical Admiral Hang Tuah Based on Pancasila Education and Citizenship - Aris Saputro; Sri Untari; Nuruddin Hady (JED (Jurnal Etika Demokrasi), 2022)
History that tells related to the Indonesian nation has been a maritime nation since long ago, including known from the history of Srivijaya and Majapahit and the famous figure of Admiral Hang Tuah. This article aims to introduce and understand the values of the educational character of the VAT-based Admiral Hang Tuah. Pocket books are small, light, and practical books containing essential and interesting information (material). The religious character education pocket book contains much information related to strengthening character education, archipelago insight, nautical culture, and character values of Admiral Hang Tuah. This type of research is the development research of the ADDIE model. The results of the discussion, first, the development of the pocket book of the character of Admiral Hang Tuah consists of five stages of development: analysis, design, development, implementation, and evaluation. Second, the feasibility of the media pocket book of character education of the character of Admiral Hang Tuah contains three things: the feasibility of the content of the book, the feasibility of language, and the feasibility of the media. Based on the overall results of the pocket book assessment, material experts, linguists, and media experts obtained a score of 4.4, with a very decent category. Based on the response of students of class VII A Junior High School Hang Tuah 4 Surabaya with a pocket book shows an average score of 4.6, which belongs to the category is very feasible. The conclusion of the development of pocket book media education of the character of the kebaharian Admiral Hang Tuah through five stages and the feasibility of pocket book media are based on the assessment of material experts, linguists, and media experts as well as the student's response to the pocket book of the character of the nautical.Sejarah yang menceritakan terkait bangsa Indonesia telah menjadi bangsa bahari semenjak dahulu, di antaranya diketahui dari sejarah Sriwijaya dan Majapahit serta terkenalnya tokoh Laksamana Hang Tuah. Tujuan dari penulisan artikel ini adalah mengenalkan dan memahami nilai-nilai pendidikan karakter kebaharian Laksamana Hang Tuah Berbasis PPKn. Buku saku merupakan buku yang berukuran kecil, ringan, dan praktis yang berisi suatu informasi (materi) penting serta menarik. Buku saku pendidikan karakter kebaharian memuat banyak hal informasi terkait penguatan pendidikan karakter, wawasan nusantara, budaya bahari, dan nilai-nilai karakter Laksamana Hang Tuah. Jenis penelitian ini adalah penelitian pengembangan model ADDIE. Hasil pembahasan, pertama, pengembangan buku saku karakter kebaharian Laksaman Hang Tuah terdiri dari lima tahap pengembangan yaitu: analisis, perancangan, pengembangan, implementasi, dan evaluasi. Kedua, kelayakan media buku saku pendidikan karakter kebaharian Laksamana Hang Tuah memuat tiga hal yaitu kelayakan isi buku, kelayakan kebahasaan, dan kelayakan media. Berdasarkan hasil keseluruhan penilaian buku saku berdasarkan ahli materi, ahli bahasa, dan ahli media memperoleh skor 4,4 dengan kategori sangat layak. Berdasarkan respon siswa kelas VII A SMP Hang Tuah 4 Surabaya dengan adanya buku saku menunjukkan skor rata-rata sebesar 4,6 yang termasuk kategori sangat layak. Kesimpulan pengembangan media buku saku pendidikan karakter kebaharian Laksamana Hang Tuah melalui lima tahap dan kelayakan media buku saku didasarkan pada penilaian dari ahli materi, ahli bahasa, dan ahli media serta respon siswa terhadap buku saku karakter kebaharian